DETERMINATION OF CONCRETE VAULT THICKNESS OF NEAR SURFACE DISPOSAL FOR RADIOACTIVE WASTE AT SERPONG NUCLEAR AREA - Sucipta Sucipta; Suhartono Suhartono (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2017)
In order to support and complement the radioactive waste management facilities in Indonesia, BATAN will build a demonstration disposal facility in Serpong Nuclear Area (SNA). Demonstration disposal that will be built is Near Surface Disposal (NSD) type. Engineered vault for NSD is reinforced concrete. The calculations for determining the thickness of NSD concrete vault is based on the conceptual design as the result of the placement optimization of demonstration disposal that takes into account the inventory of radioactive waste and environmental geology conditions of the site at Serpong Nuclear Area. The thickness of the vault in this paper is focused on its ability to withstand radiation from stored waste so that workers or people who are around the disposal facility is safe with maximum radiation dose limit rate of 0.3 μSv / h. The calculation is performed with the aid of MicroShield 7:02 and Rad Pro Calculator Version 3:26 software. From the calculation so that the dose rate at the outer surface of the vault to be 0.3 μSv / h, required walls made of concrete with a density of 2:35 g / cm3 is 62.8 cm thickness.